Rhombencephalosynapsis with Aqueductal Stenosis: A Rare Cause of Adolescent Hydrocephalus - Shashank, Raj; Vinubhai Darva, Sanket; Pushkar, Kumar (Journal of Neonatal Surgery, 2025)
Rhombencephalosynapsis (RES) is a rare congenital malformation of the hindbrain characterized by fusion of the cerebellar hemispheres due to partial or complete agenesis of the cerebellar vermis. It presents with a spectrum of neurological manifestations, including motor dysfunction, cognitive delay, and hydrocephalus secondary to aqueductal stenosis. We report the case of a 15-year-old female who presented with a six-month history of progressive headache and blurred vision, along with developmental delay. MRI revealed classic features of RES, including complete agenesis of the cerebellar vermis and fusion of the bilateral cerebellar hemispheres. Additional findings included fusion of the inferior colliculi and absence of the septum pellucidum. The supratentorial ventricular system was moderately dilated, indicating hydrocephalus secondary to stenosis at the level of the aqueduct of Sylvius. The corpus callosum appeared thinned and showed upward bowing, suggestive of chronically elevated intracranial pressure. A thinned, upward-bowed corpus callosum was noted, suggestive of chronic raised intracranial pressure. This case underscores the importance of early neuroimaging in children with neurological symptoms and developmental delay. Recognizing RES and its associated anomalies is essential for appropriate management, including CSF diversion procedures and neurodevelopmental support.